2019
DOI: 10.3127/ajis.v23i0.1893
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning, Ethics and Law

Abstract: Recent revelations concerning data firm Cambridge Analytica's illegitimate use of the data of millions of Facebook users highlights the ethical and, relatedly, legal issues arising from the use of machine learning techniques. Cambridge Analytica is, or was -the revelations brought about its demise -a firm that used machine learning processes to try to influence elections in the US and elsewhere by, for instance, targeting 'vulnerable' voters in marginal seats with political advertising. Of course, there is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…-healthcare for tasks such diagnosis and treatment recommendations (Raghu et al, 2019), -human resources for selecting who is interviewed for a job (Kim & Heo 2021), -the judicial system for sentencing or for establishing eligibility for bail or parole (Kleinberg et al, 2017) -public administration for establishing eligibility to social assistance programmes (Booth, 2019), -police forces for deciding where to increase patrolling or for identifying suspects (facial recognition) (Miller 2019a;Ratnaparkhi et al, 2021) -universities for admission in academic programmes (Newton, 2021). This very partial list shows how we are currently in the process of automating decision making in crucial areas of social life.…”
Section: Machine Learning's Explainability Problemmentioning
confidence: 99%
“…-healthcare for tasks such diagnosis and treatment recommendations (Raghu et al, 2019), -human resources for selecting who is interviewed for a job (Kim & Heo 2021), -the judicial system for sentencing or for establishing eligibility for bail or parole (Kleinberg et al, 2017) -public administration for establishing eligibility to social assistance programmes (Booth, 2019), -police forces for deciding where to increase patrolling or for identifying suspects (facial recognition) (Miller 2019a;Ratnaparkhi et al, 2021) -universities for admission in academic programmes (Newton, 2021). This very partial list shows how we are currently in the process of automating decision making in crucial areas of social life.…”
Section: Machine Learning's Explainability Problemmentioning
confidence: 99%
“…Miller (2019) focussed on three areas in legal domains in which machine learning techniques are commonly used: adjudication in law, profiling and predictive policing, and a machine's compliance with legally enshrined moral principles. He concluded that while machine learning techniques have considerable actual and potential benefits, they also have, limitations, and both actual and potential ethical downsides.…”
Section: Problems Related To the Use Of Machine Learning In Making Le...mentioning
confidence: 99%
“…Analysis in [32] has shown that profiling can give rise to problems at the interface of law and ethics. Author concluded that profiling is potentially inconsistent with the individual rights of citizens in liberal democracies.…”
Section: Labelling and Profilingmentioning
confidence: 99%